Deep-Sea Cold Seep Campylobacterota: Diversity, Growth, Metabolic Characteristics, and Nutrient Production - Xiaoman Yan; Qinglei Sun; Ke Xu; Jintao Zhuo; Yuanyuan Sun; Guowei Qian; Xin Zhang; Li Sun (Microorganisms)
Deep-sea chemosynthetic ecosystems, including cold seeps and hydrothermal vents, are widely spread in global oceans. Campylobacterota are important primary producers in deep-sea hydrothermal vents and serve as a vital food source for local invertebrates. However, the nutrients that these bacteria can provide to their hosts are unclear. To date, research on Campylobacterota in cold seeps is very limited. Consequently, little is known about the biological features and ecological potential of Campylobacterota in cold seeps. In the present work, we examined the diversity, growth, metabolic characteristics, and nutrient production of Campylobacterota in a deep-sea cold seep. Over 1000 Campylobacterota ASVs, especially autotrophic Sulfurovum and Sulfurimonas, were identified. By optimizing the culture medium, 9 Sulfurovum and Sulfurimonas strains were isolated, including three potentially novel species. Two novel species were characterized and found to exhibit unique morphological features. These two novel strains possessed complete reverse tricarboxylic acid pathways. One novel strain, FCS5, was a psychrotolerant autotroph with denitrification and phosphorus-removing capacity. FCS5 could grow in the absence of vitamins. Consistently, metabolomics and transcriptome analyses indicated that FCS5 produced multiple vitamins, which regulated the expressions of a large number of genes associated with carbon fixation and multiple-nutrient synthesis. Besides vitamins, autotrophic Campylobacterota also produced abundant free amino acids, fatty acids (short-chain, medium, and long-chain), and proteins. This study indicates that the cold seep abounds with Campylobacterota, which are capable of providing various nutrients for the chemosynthetic ecosystem. In addition, these bacteria may have wide applications, such as in wastewater treatment and carbon emission reduction.